2014
DOI: 10.1007/s12035-014-8997-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Variants in CHRNA5/A3/B4 Gene Cluster on Chromosome 15 to Tobacco Smoking: From Genetic Association to Mechanism

Abstract: Cigarette smoking is the major cause of preventable death and morbidity throughout the world. Many compounds are present in tobacco, but nicotine is the primary addictive one. Nicotine exerts its physiological and pharmacological roles in the brain through neuronal nicotinic acetylcholine receptors (nAChRs), which are ligand-gated ion channels consisting of five membrane-spanning subunits that can modulate the release of neurotransmitters, such as dopamine, glutamate, and GABA and mediate fast signal transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 96 publications
0
43
0
9
Order By: Relevance
“…Some of the first GWA studies showed that variations in the sequence of α3, α5, and β4 nAChR subunit genes affects the risk for developing and maintaining a nicotine addiction (Berrettini et al 2008; Chen et al 2009; Liu et al 2010; Wen et al 2016). More recent genetic studies revealed that variability in the α4 nAChR subunit gene affects the risk for developing nicotine addiction in humans (Hancock et al 2015; Thorgeirsson et al 2016).…”
Section: Genetic Variation In Hypocretin and Galanin Receptor Genementioning
confidence: 99%
“…Some of the first GWA studies showed that variations in the sequence of α3, α5, and β4 nAChR subunit genes affects the risk for developing and maintaining a nicotine addiction (Berrettini et al 2008; Chen et al 2009; Liu et al 2010; Wen et al 2016). More recent genetic studies revealed that variability in the α4 nAChR subunit gene affects the risk for developing nicotine addiction in humans (Hancock et al 2015; Thorgeirsson et al 2016).…”
Section: Genetic Variation In Hypocretin and Galanin Receptor Genementioning
confidence: 99%
“…One of the most robust findings in genome-wide association studies is that variants in the CHRNA5 / A3 / B4 cluster on chromosome 15q24-25.1 show a significant association with both nicotine dependence and lung cancer 10 . However, current genetics-based evidence is lacking for elucidating the carcinogenic mechanisms of cigarette smoking-associated cancers, which leads many researchers to focus on the function of smoking-associated DNA methylation (SA-DNAm).…”
Section: Introductionmentioning
confidence: 99%
“…From the various subtype combinations of nAChRs known, the highly abundant heteromeric α4β2* (* indicates possible other subunits present) subtype is linked to the positive reinforcing effects of nicotine [1618] and is the target for varenicline, which acts as a partial agonist at this nAChR subtype to reduce the rewarding effect of nicotine in humans and in animal models of nicotine self-administration [11, 19]. Recent findings from human genetic studies and preclinical mouse models show that other nAChR subtypes present in the brain also play an important role in the dependence and reinforcing effects of nicotine [2023]. …”
Section: Introductionmentioning
confidence: 99%